Robust speed estimation for tacholess induction motor drives - Choi, Ick; Kwon, SH; Lim, J; Hong, SW (IEE-INST ELEC ENG, 1996)
A model-reference adaptive system (MRAS) based speed estimation scheme for tacholess induction motor drives is presented, which is robust to variations in stator resistance and leakage inductance values over a wide speed range. The estimated speed is used as feedback in a vector control system. Theoretical consideration and simulation results showing its effectiveness are presented.
Keywords: VECTOR CONTROL; IDENTIFICATION